Assessment of aspirin resistance varies on a temporal basis in patients with ischaemic heart disease. Issue 15 (12th August 2008) - Muir, A R; McMullin, M F; Patterson, C; McKeown, P P
Abstract : Objective: Laboratory tests including optical platelet aggregometry (OPA), platelet function analyser (PFA-100), and thromboxane B2 (TXB2 ) metabolite levels have been used to define aspirin resistance. This study characterised the prevalence of aspirin resistance in patients with ischaemic heart disease (IHD) and investigated the concordance and repeatability of these tests. Design, setting and patients: Consecutive outpatients with stable IHD were enrolled. They were commenced on 150 mg aspirin daily (day 0) and had platelet function assessment (OPA and PFA-100) and quantitative analysis of serum/urine TXB2 at day ⩾7 and then at a second visit approximately 2 weeks later. Main outcome measures: We assessed the prevalence of aspirin resistance by each method, concordance between methods of measuring response to aspirin and association between time points to assess the predictability of response over time. Results: 172 patients (62.7 (SD 8.7) years, 83.1% male) were recruited. At visits 1 and 2, respectively, 1.7% and 4.7% were aspirin resistant by OPA, whereas 22.1% and 20.3% were aspirin resistant by PFA-100. There were poor associations between PFA-100 and OPA, and between TXB2 metabolites and platelet function tests. OPA and PFA-100 results were poorly associated between visits (κ = 0.16 and κ = 0.42, respectively) as were TXB2 metabolites, suggesting that aspirin resistance is not predictable over time. Conclusions: The prevalence of aspirin resistance is dependent on the method of testing. Response varies on a temporal basis, indicating that testing on a single occasion is inadequate to diagnose resistance or guide therapy in a clinical setting.